Coincidence Points Under Weak Contractions on Symmetric Spaces - Latif , Abdul; Abou-Hajar, A. A. (Sarajevo Journal of Mathematics, 2024)
In this paper we prove some results on the existence of coincidence points for weak hybrid contractions on symmetric spaces. These results improve and generalize some known results. In particular, recent fixed point results due to Hicks [3] are generalized. 2000 Mathematics Subject Classification. 47H10, 54H25